VERBAL FLUENCY IN CHILDREN WITH INTELLECTUAL DISABILITY: INFLUENCE OF BASIC EXECUTIVE COMPONENTS - Gligorović, Milica; Buha, Nataša (Specijalna edukacija i rehabilitacija, 2014)
Phonemic and semantic fluency tasks are frequently used to differentiate executive control roles and the integrity of lexical-semantic representation. The main goal of this study is to determine the influence of basic executive components on phonemic and semantic productivity in children with mild intellectual disability. The sample consisted of 95 children with unspecified mild intellectual disability (MID), ages 10-13.11. Phonemic fluency was assessed by the Controlled Oral Word Association Test (COWAT), while semantic fluency was assessed by the Category Naming Test (CNT). Cognitive flexibility was assessed by Wisconsin Card Sorting Test (WCST) and Trail Making Test (TMT). Number Manipulation Task (NMT) was used for the verbal working memory assessment, while Day/Night Stroop Task was used for the assessment of inhibitory control. The results analysis showed that all of the assessed EF components significantly affect phonemic productivity. Semantic productivity significantly depends on WCST and TMT performance. Verbal working memory and inhibitory control do not significantly contribute to semantic productivity. The results of our study indicate that the discrepancy between phonemic and semantic productivity in children with MID could be directly associated with the basic executive functions components. Key words: verbal fluency, executive functions, mild intellectual disability